Scoprire il disinteresse estetico; attualità e critiche di un concetto filosofico (Itinera, 2025)
Discovering Aesthetic Disinterestedness; relevance and critiques of a Philosophical ConceptThis article addresses the complexity of the concept of “aesthetic disinterestedness”, offering an in-depth analysis through the contributions of significant philosophical texts, including those by Jerome Stolnitz, Thomas Hilgers, and Maria Alina Asavei. Originally associated with the contemplation of natural beauty, aesthetic disinterestedness emerges as a core principle in the artistic experience, as well as in individual self–determination.The text explores the implications of this attitude within the context of a more politicized contemporary artistic practice, where disinterest assumes the role of a mode of creative interaction, capable of generating new awareness and interpretations of reality. In light of these theoretical insights and other exemplary cases, the article responds to the invitation to present contributions that delve into paradigmatic aspects of the complex evolution of contemporary configurations of classical and post–Kantian theories of aesthetic disinterestedness and their original reinterpretations in the contemporary era.
Keywords: aesthetic; philosophy; disinterest; contemporary art